Anatomical Study for Vegetative Organs of Pelargonium graveolens L.'Hér Cultivated in Iraq - Nassrullah, Israa; Noori Mohamed, Marwan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The current investigation concluded an  anatomical study of the cultivated species Pelargonium graveolens  L. 'Hér belong to the  Geraniaceae family and which  cultivated as an  ornamental plant, fresh specimen were collected from different region  in  Baghdad ,the study vegetative parts (leaf, stem and petiole) in details ,the upper and lower epidermis of leaf and epidermis of  stem  also studied, ordinary epidermal cells and stomatal complexes studied in term of shapes and  dimensions  ,the result showed that stomatal in leaf and stem is anomocytic type, the cross sections of the vegetative parts  prepared by microtome and free hand sectioning. The tissues of these parts include the number and the type of layers and thickness of each one  , the result showed the presence of druses crystals in parenchyma cells of the petiole, stem and leaf. Vistur type of this organs also studied and it comprises of glandular and non-glandular trichomes which occur in different types and lengths.